Immunosenescence : Penuaan Pada Sel Makrofag - Fajri Marindra Siregar (Jurnal Ilmu Kedokteran, 2019)
Immune function will decrease with age. The weakening of immune system is known as immunosenescence. Macrophages that play a major role in carrying out innate and adaptive immune functions have potential to undergo aging (macrophaging). Some potential mechanisms that can affect the aging of macrophages include telomere shortening, oxidative damage and impaired DNA repair processes. The impact of macrophaging can be a decrease number of macrophages in bone marrow, changing cytokine secretion, decreasing class II MHC expression, changing macrophages polarization, decreasing ability of phagocytosis, and decreasing ability of wound repair and tissue regeneration.